Pendidikan 4.0: Perubahan paradigma dan penguatan kearifan lokal dalam pembelajaran matematika - Benny N. Trisna (STKIP PGRI Banjarmasin, 2019)
The industrial revolution 4.0 brings convenience as well as challenges to change, not only in the industrial world, but also in the field of education. Efforts are needed to harmonize the world of education with changes in the era of disruptive technology. This paper describes imapcts of industrial revolution for education field as well as anticipation and changes that must be made in the field, including efforts to keep alive and to reinforce local wisdom, especially in mathematics education. Beginning with changing the perspective of students, the perspective on technology, familiarizing students with collaboration and teamwork, reorienting the curriculum, reorienting assessment, using blended learning, honing 4C skills (critical tinking, creativity, collaboration, and communication), and encourage universities to facilitate life-long learning. Reinforcement of local wisdom also needs to be done. Besides through local content subjects, reinforcement of local wisdom can also be done by integrating local culture and wisdom in aspects of learning methodology and learning content. The results of researches in the field of ethnomatematics can be used as a reference to integrate and to reinforce local culture and wisdom in learning mathematics.